2019
DOI: 10.1002/pchj.274
|View full text |Cite
|
Sign up to set email alerts
|

Setting the beat of an internal clock: Effects of dexamphetamine on different interval ranges of temporal processing in healthy volunteers

Abstract: Drug studies are powerful models to investigate the neuropharmacological mechanisms underlying temporal processing in humans. This study administered dexamphetamine to 24 healthy volunteers to investigate time perception at different time scales, along with contributions from working memory. Healthy volunteers were administered 0.45 mg/kg dexamphetamine or placebo in a doubleblind, crossover, placebo-controlled design. Time perception was assessed using three experimental tasks: a time-discrimination task, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 117 publications
(171 reference statements)
1
15
0
Order By: Relevance
“…In general, regardless of the induction method, ASC can be characterized by changes in the sense of self and time (Berkovich‐Ohana & Wittmann, 2017; Wittmann, 2015, 2018; Wittmann et al, 2019). Subjective changes in the passage of time and its perceived duration have been studied with different induction methods such as hypnosis (Lush & Dienes, 2019), meditation (Droit‐Volet & Dambrun, 2019; Singh & Srinivasan, 2019), and pharmaceutical agents (Graham‐Schmidt, Martin‐Iverson, & Waters, 2019), including psychedelics (Wittmann et al, 2007). In a recent study that used a special Ganzfeld technique where participants sit in an egg‐shaped, whole‐body perceptual deprivation chamber, the reported experience of time proved quite distorted (Glicksohn, Berkovich‐Ohana, Mauro, & Ben‐Soussan, 2017).…”
mentioning
confidence: 99%
“…In general, regardless of the induction method, ASC can be characterized by changes in the sense of self and time (Berkovich‐Ohana & Wittmann, 2017; Wittmann, 2015, 2018; Wittmann et al, 2019). Subjective changes in the passage of time and its perceived duration have been studied with different induction methods such as hypnosis (Lush & Dienes, 2019), meditation (Droit‐Volet & Dambrun, 2019; Singh & Srinivasan, 2019), and pharmaceutical agents (Graham‐Schmidt, Martin‐Iverson, & Waters, 2019), including psychedelics (Wittmann et al, 2007). In a recent study that used a special Ganzfeld technique where participants sit in an egg‐shaped, whole‐body perceptual deprivation chamber, the reported experience of time proved quite distorted (Glicksohn, Berkovich‐Ohana, Mauro, & Ben‐Soussan, 2017).…”
mentioning
confidence: 99%
“…( 2000 ) demonstrated that despite the lack of main effects, dexamphetamine (0.25 mg/kg) enhanced SWM performance on n ‐back tests in those subjects who had lower baseline capacity, while it impaired SWM performance in those subjects who had relatively higher baseline capacity. Likewise, dexamphetamine (0.45 mg/kg) enhanced VWM performance on digit span task in those subjects who had lower baseline capacity, but not in those subjects who had relatively higher baseline capacity (Graham‐Schmidt et al., 2019 ). Another fMRI study has shown that dexamphetamine‐induced dopamine release in older healthy individuals increased brain signal variability during the WM task, comparable to or exceeding the brain signal variability young adults had in the placebo condition (Garrett et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar sizes and numbers of capsules containing either placebo (glucose) or 0.45 mg/kg dexamphetamine were prepared using 1, 2.5, 5, and 10 mg dexamphetamine sulfate tablets. This dose of dexamphetamine was selected based on previous experiments in healthy subjects demonstrating significant effects on a range of illusory and psychophysiological measures (Albrecht et al, 2011(Albrecht et al, , 2012Graham-Schmidt et al, 2019;Woodward et al, 2011).…”
Section: Drug and Designmentioning
confidence: 99%